EVALUATION OF THE EFFICIENCY OF THE ENTERPRISE WITH THE HELP KPI - Семененко, Юрий (SWorldJournal, 2021)
The article analyzes the methods of assessing the effectiveness of the modern enterprise. The main approaches to assessing the efficiency of the enterprise are analyzed and systematized. The use and implementation of key performance indicators (KPIs) is